Problem-based learning: Assessing students' mathematical communication in story problems - Yus Mochamad Cholily; Makrifatul Khoiriyah; Alfiani Athma Putri Rosyadi; Akhsanul In’am (Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
Students often have difficulty solving mathematical word problems because they must interpret contextual information, construct mathematical representations, and clearly communicate their reasoning. These challenges are closely related to students’ mathematical communication skills, which play an important role in supporting conceptual understanding and problem solving. Therefore, this study aims to describe students’ mathematical communication skills during the implementation of the Problem-Based Learning (PBL) model in solving word problems on lines and angles. This research employed a qualitative descriptive approach conducted at SMP Negeri 3 Plumpang, Tuban, involving seven seventh-grade students selected through purposive sampling based on different levels of academic ability. Data were collected through written tests, classroom observations, and documentation, and analyzed using an interactive qualitative analysis consisting of data reduction, data display, and conclusion drawing. The results show that students’ mathematical communication skills vary across ability levels. Students in the high category were able to present accurate visual representations, use mathematical notation correctly, and explain solution steps clearly and coherently. Students in the medium category were able to use mathematical symbols and provide explanations but still showed limitations in constructing visual representations. Meanwhile, students in the low category had difficulty representing problems and expressing mathematical ideas systematically. These findings indicate that implementing PBL can support the development of students’ mathematical communication skills through collaborative discussion and problem-solving activities. This study contributes to a deeper understanding of how mathematical communication skills emerge during PBL-based learning in mathematics classrooms.